PCL-gelatin honey scaffolds promote Staphylococcus aureus agrA expression in biofilms with Pseudomonas aeruginosa - Hilliard, Genevieve M.; Wilkinson, Thomas Stephens; Harris, Llinos G.; Jenkins, Rowena E.; Shornick, Laurie P. (Frontiers in Microbiology, 2024)
Introduction Bacterial infection and biofilm formation contribute to impaired healing in chronic diabetic wounds. Staphylococcus aureus and Pseudomonas aeruginosa are found in human diabetic wound biofilms. They may develop antibiotic resistance, increasing the urgency for alternative or complementary therapies. Diabetic wound healing may be improved with the use of biomedically engineered scaffolds, which can also serve as delivery systems for antibacterial compounds. Manuka honey is a potent antibacterial and wound care agent due to its high osmolarity, low pH, and constituents (such as methylglyoxal). Honey exhibits bacteriostatic and bactericidal effects, modulates the expression of biofilm forming genes, and restores antibiotic susceptibility in previously drug resistant pathogens. Methods In this study, we created a dermal regeneration template (DRT) composed of polycaprolactone-gelatin (PCL-gelatin) and Manuka honey to retain honey in the wound and also provide a scaffold for tissue regeneration. Results and discussion Soluble Manuka honey inhibited the planktonic and biofilm growth of both S. aureus (UWH3) and P. aeruginosa (PA14) co-cultures. Manuka honey embedded PCL-gelatin scaffolds did not exhibit bacteriostatic or bactericidal effects on cocultures of UHW3 and PA14; however, they promoted the expression of AgrA, a gene associated with dispersal of S. aureus biofilms.